From discord to harmony : making your workplace hum - Wilkin, LaVena; Belak, Tony (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Conflicts happen, and the workplace can be a breeding ground for negative conflicts. Consider that organizational culture consists of shared values, beliefs, assumptions, perceptions, and norms. Add to that the fact that organizations are multifaceted associations of individuals, departments, and divisions, and each is competing for scarce resources. Stir in a little power imbalance and organizational political posturing. Then, add the fact that today's managers are faced with diversity and cultural issues ranging from race and gender to individual ethnicity, principles, and philosophies, about which we are more vocal. Shake all that together and you have a workplace that is bubbling over with conflicted people and situations. However, when productively managed, conflicts can be the lifeblood of an organization. Consider that music is not a single note. Rather, it is the silence between the notes that make beautiful music. Conflict is the silence between the notes. Unfortunately, conflict has a bad reputation, and it is often labeled as disagreement, fighting, or arguing that leads to stress, retaliation, and resentment. Even though managers spend between 40% and 60% of their days dealing with conflicts, many have not learned what causes conflicts or how to productively manage them, so they avoid or force outcomes. As a result, discord abounds and results in fractured relationships, loss of productivity, and even lawsuits. Learning to fine tune the conflicts will help managers orchestrate a more harmonious workplace"--